(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific article presents the results of a survey of teaching staff, which was conducted to identify obstacles and determine key components for the formation of a digital model that will be aimed at increasing the level of physical activity and raising the level of patriotic education among schoolchildren in the context of modern challenges and threats. The survey of teaching staff (n = 69) was conducted online using a Google Form. The questionnaire covered current barriers, needs, opportunities, and expected digital solutions. Respondents ranked the main factors that, in their opinion, hinder physical activity and the formation of patriotic consciousness among schoolchildren. The study aimed to identify the main barriers and key components for developing a modern digital model for increasing the level of physical activity and patriotic education of schoolchildren based on an expert survey of teaching staff. The results of the study of teaching staff indicate that the key barriers to increasing physical activity and patriotic education among schoolchildren are insufficient funding, limited material and technical resources, and excessive overload with theoretical material. Respondents most often cited encouraging students to participate in activities, developing the appropriate infrastructure, and providing systematic support for teachers’ professional growth as priority areas for investment. The most significant components of the future digital model were interactivity, online access to educational materials, a personalised approach to students, and administrative and collegial support. The importance of integrating patriotic content as a mandatory element of the digital model received high support among respondents. Thus, analysing barriers and identifying key components serve as the basis for building a modern digital model capable of effectively promoting increased physical activity and patriotic education among schoolchildren in today’s challenges and threats. The generalised results of the survey form the scientific basis for creating a structured, adaptive, and effective digital model that will meet the needs of modern school education in martial law conditions.